Development and characterization of nano-bilayer films composed of polyvinyl alcohol, chitosan and alginate. (April 2018) - Zhuang, Chenjun; Jiang, Yongli; Zhong, Yu; Zhao, Yanyun; Deng, Yun; Yue, Jin; Wang, Danfeng; Jiao, Shunshan; Gao, Haiyan; Chen, Hangjun; Mu, Honglei
Abstract: Polyvinyl alcohol (PVA), sodium alginate (SA) and chitosan (CHI) are all biodegradable materials with excellent film-forming properties. This study prepared bilayer films with PVA-CHI film as the outer layer and SA film as the inner layer. Fuzzy comprehensive evaluation was used to study the effects of the SA film formula where nano-cellulose, surfactant, calcium chloride and anti-bacterial agents were added. The performance of the bilayer films was evaluated considering water solubility, water barrier, mechanical and antibacterial properties. And the effects of the coatings on qualities of shell eggs were investigated. The results demonstrated that the bilayer film possessed lower water vapor permeability (WVP) than the single-layer one, and water droplet was more difficult to spread on bilayer film. Increasing the content of SA significantly increased ( p  ≤  0.05 ) the mechanical properties of bilayer film, and the tensile strength (TS) increased 1.8 times when the SA content increased from 1 to 2%. Calcium chloride decreased the film solubility, and Tween 80 reduced the surface tension of the film-forming solution. Moreover, ethyl paraben sodium significantly increased the antibacterial activity of the bilayer film against E.coli and L . innocua, but had negative impact on TS and WVP. According to the orthogonal test L9 (3 4), the optimal formula of SA layer was: SA 1.25%, calcium chloride 0.75%, Tween 80 0.175%, and ethyl paraben sodium 0.125%. In addition, coatings reduced weight loss, and maintained Haugh unit and yolk index of shell eggs during 15 days of storage at 25 °C, especially bilayer coating. Highlights: Bilayer films were developed from polyvinyl alcohol, chitosan and alginate. Bilayer films showed improved water barrier properties compared with monolayer films. The performance index of the film increased with increasing nano-cellulose contents. Ethyl paraben sodium had an inhibitive effect against E.coli and Listeria .